2017
DOI: 10.1002/pits.22007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Functional Behavior Assessment on School‐based Interventions: A Meta‐analysis of Single‐case Research

Abstract: The effectiveness of behavior reduction strategies is likely affected by any number of ancillary variables. The purpose of this study was to provide a quantitative review of school‐based behavior reduction interventions and some ancillary variables that may modulate the effectiveness of those interventions. Tau‐U, an effect size statistic for single‐case designs that takes into account level and trend, was calculated across studies, allowing for examination of several moderator variables including type of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…The present meta-analysis reviewed the literature on the use of FBAs with youth in kindergarten through 12 th grade who either had high incidence disabilities or were at risk for and displayed challenging behaviors in classroom settings during academic related tasks/activities. Calculated effect sizes were commensurate to those obtained by other reviewers (e.g., Bruni et al, 2017;Losinski et al, 2014;Miller & Lee, 2013). No previous review calculated CDC lines in order to determine the percentage of systematic change (71% of AB contrasts), and only 40% of studies reported social validity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The present meta-analysis reviewed the literature on the use of FBAs with youth in kindergarten through 12 th grade who either had high incidence disabilities or were at risk for and displayed challenging behaviors in classroom settings during academic related tasks/activities. Calculated effect sizes were commensurate to those obtained by other reviewers (e.g., Bruni et al, 2017;Losinski et al, 2014;Miller & Lee, 2013). No previous review calculated CDC lines in order to determine the percentage of systematic change (71% of AB contrasts), and only 40% of studies reported social validity.…”
Section: Discussionsupporting
confidence: 72%
“…It is believed that the most effective interventions implemented in school and clinical settings are those based on the purpose maladaptive behaviors serve (Ervin et al, 2001). There have literally been hundreds of studies conducted on various aspects of FBA methodologies across different participant characteristics, and approximately 17 systematic reviews have been conducted on various procedures and populations-eight of which used meta-analytic approaches to calculate effect sizes (Bruni et al, 2017;Common, Lane, Pustejovsky, Johnson, & Johl, 2017;Delfs & Campbell, 2010;Gage, Lewis, & Stichter, 2012;Goh & Bambara, 2012;Losinski, Maag, Katsiyannis, & Ennis, 2014;McKenna, Flower, Kim, Ciullo, & Haring, 2015;Miller & Lee, 2013). Some of the variables addressed in these reviews included, but were not limited to, single case synthesis, effect size approaches, different populations, quality of studies, and positive supports in schools and clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for each classroom, percentage of data points exceeding the median (PEM) was calculated by determining the percentage of data points in the intervention and maintenance phases exceeding the median data point in the baseline phase and then dividing by 100 (Ma, 2006). Although Ma (2006) suggested PEM interpretation guidelines, more conservative guidelines for nonparametric effect size values were applied (Bruni et al, 2017;Parker & Vannest, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For each classroom, effect size estimates (i.e., PEM) were calculated comparing baseline-phase data to both intervention-and maintenance-phase data (see Table 2). PEM values from .93 to 1 were considered large, from .66 to .92 were medium, and below .65 were small (Bruni et al, 2017;Parker & Vannest, 2009). When comparing baseline phases to intervention phases, effect sizes for Classrooms A and B were medium and the effect size for Classroom C was large.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also conducted Tau-U analyses (Parker, Vannest, Davis, & Sauber, 2010) to compare the averages between phases using an online calculator (Vannest, Parker, Gonen, & Adiguzel, 2016). Baseline data were compared with intervention data and corrected when the trend of baseline data was increasing to the point it could have confounded the researcher’s interpretation of the effectiveness of the intervention (Bruni et al, 2017). Researchers did not correct for baseline instances of clear differences between baseline and intervention data points.…”
Section: Methodsmentioning
confidence: 99%